Stephens Standard, December 1920 - Stephens College Students (Stephens College, 1920)
Volume 1 Number 1; The Stephens Standard magazine provided news about curricular changes, departmental programs, building projects, land acquisition for expansion, the whereabouts of graduates, and sorority and other social functions. It also provided biographical sketches and achievements of faculty and staff, as well as student creative works such as short fiction, non-fiction, poetry, illustration, and photography.